Nilai Waktu Uang dalam Pengambilan Keputusan Keuangan: Tinjauan Literatur atas Perspektif Konvensional dan Syariah - Amelia Ayudia; Vindy Sanjaya; Muhammad Fahim (Indo Publishing, 2026)
The concept of time value of money is a fundamental principle in finance. Basically, the value of money can change over time. In conventional finance, this principle is often used to make decisions on investment, financing, and long-term financial planning. However, in Sharia finance, this concept is often debated because it is related to interest, which is prohibited in Sharia law itself. This article aims to explore how the concept of time value of money is applied, both from a conventional and Sharia perspective. This research was conducted through a systematic literature study method by reviewing various scientific articles from SINTA-accredited journals and reliable sources on Google Scholar published between 2019 and 2025. This approach was chosen to gain a better understanding of conventional finance, which views money as a commodity whose value can increase over time. Meanwhile, Islamic finance places greater emphasis on the economic value of time, how time is used in productive activities, rather than just interest or nominal growth. This difference in perspective has a major impact on financial decision-making, accounting practices, and the management of financial institutions. Therefore, understanding these two perspectives is very important so that the decisions made are not only efficient but also in accordance with the principles adopted.